2015
DOI: 10.1002/hep.27674
|View full text |Cite
|
Sign up to set email alerts
|

Low risk of liver decompensation among human immunodeficiency virus/hepatitis C virus–coinfected patients with mild fibrosis in the short term

Abstract: Liver fibrosis is used to make decisions about the timing of therapy against hepatitis C virus (HCV) in routine clinical practice, which should be based on the short-term likelihood of liver decompensations. Thus, we aimed at evaluating the risk of decompensations and death among human immunodeficiency virus (HIV)/HCV-coinfected individuals according to their baseline fibrosis classified by either liver biopsy or liver stiffness measurement (LSM). Patients coinfected with HIV/HCV, naive or without sustained vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Our findings are similar to a previous study by Merchante and colleagues where patients with cirrhosis had an incidence of hepatic decompensation of 46 per 1000 PY [32]. Similarly, Macías et al reported that patients with LSM <14.6 kPa have a lower risk of decompensation [35]. However, these studies did not differentiate between patients with and without clinical evidence of liver cirrhosis.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are similar to a previous study by Merchante and colleagues where patients with cirrhosis had an incidence of hepatic decompensation of 46 per 1000 PY [32]. Similarly, Macías et al reported that patients with LSM <14.6 kPa have a lower risk of decompensation [35]. However, these studies did not differentiate between patients with and without clinical evidence of liver cirrhosis.…”
Section: Discussionsupporting
confidence: 89%
“…These results are a proof of concept, and more studies are needed to precisely determine the value of the information obtained by repeated measurements, especially for survival without liver complications, and to identify the risk of ascites, encephalopathy, variceal bleeding or HCC. The aim of one recent study was to evaluatethe risk of decompensation and death in human immunodeficiency virus (HIV)/HCV‐co‐infected individuals according to baseline fibrosis determined by either liver biopsy or LSM . Patients with HIV/HCV co‐infection who were treatment‐naive or who had not achieved a SVR to HCV therapy were included in this cohort.…”
Section: The Short‐term Prognosis Of Patients With Mild Disease Is Exmentioning
confidence: 99%
“…The adjusted hazard ratio for patients with LSM and the 95% CI for death by LSM were as follows: 6-9.4 kPa, 1.7 (0.63-4.79), P = 0.288; 9.5-14.5 kPa, 3.38 (1.2-9.5), P = 0.021; ≥14.6 kPa, 12.7 (4.9-33.6), P < 0.0001. The adjusted subhazard ratio for patients with LSM and the 95% CI by LSM category were as follows: 6-9.4 kPa, 1.89 (0.18-20.3), P = 0.599; 9.5-14.5 kPa, 6.59 (0.73-59.2), P = 0.092; ≥14.6 kPa, 59.5 (8.3-427), P < 0.0001 (13). In summary, patients co-infected with HIV/HCV without advanced fibrosis are at a very low risk of shortterm decompensation or death suggesting that deferring HCV therapy for a few years and monitoring the progression of fibrosis is a safe option.…”
mentioning
confidence: 92%
“…As patients with advanced liver disease are at considerable risk for hepatic decompensation and death [22], they represent the frontline in the use of IFN-free regimens. Combining treatmentnaïve and treatment-experienced patients receiving 12 weeks of SOF/DCV in the ALLY-2 study, the SVR rate among patients with advanced liver fibrosis treated for 12 weeks was 97%.…”
Section: Discussionmentioning
confidence: 99%
“…[15]. However, as patients with advanced liver disease are at considerable risk for hepatic decompensation and death [22], they have an urgent need for effective treatment options.…”
Section: Introductionmentioning
confidence: 99%